2017
DOI: 10.1111/scd.12221
|View full text |Cite
|
Sign up to set email alerts
|

Oral health needs, dental care utilization, and quality of life perceptions among Oregonian seniors

Abstract: Clackamas county senior population has considerable oral health needs, dental utilization, and quality of life issues. Better dental insurance plans, health literacy opportunities and culturally competent dental providers may help to improve the oral health situation and reduce barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
1
14
2
1
Order By: Relevance
“…The questionnaire allowed the identification of the Research, Society andDevelopment, v. 9, n. 11, e2639119911, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9911 domains with a more influential negative contribution to OHRQoL before the intervention, that is, the factors that resulted in demand for dental treatment. Among those, physical pain and psychological discomfort were the most significant, similarly to previous findings (Kohli et al, 2017), especially related to conditions such as edentulism and the need for a prosthesis (Bramanti et al, 2013;Lundegren et al, 2019). Tooth loss and edentulism are relevant oral health problems in elders, interfering in the masticatory capacity, malnutrition and associated morbidities, self-esteem, and other psychological aspects related to the quality of life.…”
Section: Resultssupporting
confidence: 77%
“…The questionnaire allowed the identification of the Research, Society andDevelopment, v. 9, n. 11, e2639119911, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9911 domains with a more influential negative contribution to OHRQoL before the intervention, that is, the factors that resulted in demand for dental treatment. Among those, physical pain and psychological discomfort were the most significant, similarly to previous findings (Kohli et al, 2017), especially related to conditions such as edentulism and the need for a prosthesis (Bramanti et al, 2013;Lundegren et al, 2019). Tooth loss and edentulism are relevant oral health problems in elders, interfering in the masticatory capacity, malnutrition and associated morbidities, self-esteem, and other psychological aspects related to the quality of life.…”
Section: Resultssupporting
confidence: 77%
“…All reported associations regarding edentulism, number of teeth, number of missing teeth, and number of occluding pairs are shown in Table 2. Five studies reported significantly lower OHQoL in edentulous participants than in dentate participants (Hoeksema et al, 2017;Hoeksema et al, 2018;Motallebnejad, Mehdizadeh, Najafi, & Sayyadi, 2015;Stromberg, Holmen, Hagman-Gustafsson, Gabre, & Wardh, 2013;Zuluaga, Montoya, Contreras, & Herrera, 2012), two studies demonstrated a positive association between edentate patients in comparison to dentate patients and OHQoL (Lee, Yang, Ho, & Lee, 2012;Souza, Costa Oliveira, & Martins, 2017), and seven studies reported no significant association between edentulism and OHQoL (Alshammari, Baseer, Ingle, Assery, &Al Khadhari, 2018;Cornejo, Perez, de Lima, Casals-Peidro, & Borrell, 2013;Dahl, Wang, Holst, & Ohrn, 2011;Kohli, Sehgal, Nelson, & Schwarz, 2017;Rebelo, Cardoso, Robinson, & Vettore, 2016;Sheiham et al, 2001;Yu, Lee, Hong, Lau, & Leung, 2008). All studies regarding edentulism were crosssectional studies.…”
Section: Natural Dentitionmentioning
confidence: 99%
“…This OHIP-14 has been widely used across the world for various research purposes with modifications including language and regional concerns. Assessing the adult oral health-related quality of life is one of the primary needs [1, 4, 1-8]. …”
Section: Introductionmentioning
confidence: 99%